Tumor necrosis factor receptor I blockade shows that TNF-dependent and independent mechanisms synergise in TNF receptor associated periodic syndrome - Fairclough, Lucy C.; Stoop, A.A.; Negm, Ola H.; Radford, Paul; Tighe, Patrick J.; Todd, Ian (Wiley, 2015)
TNF receptor associated periodic syndrome (TRAPS) is an autoinflammatory disease involving recurrent episodes of fever and inflammation. It is associated with autosomal dominant mutations in TNF receptor superfamily 1A gene localised to exons encoding the ectodomain of the p55 TNF receptor, TNF receptor-1 (TNFR1). The aim of this study was to investigate the role of cell surface TNFR1 in TRAPS, and the contribution of TNF-dependent and TNF-independent mechanisms to the production of cytokines. HEK-293 and SK-HEP-1 cell lines were stably transfected with WT or TRAPS-associated variants of human TNF receptor superfamily 1A gene. An anti-TNFR1 single domain antibody (dAb), and an anti-TNFR1 mAb, bound to cell surface WT and variant TNFR1s. In HEK-293 cells transfected with death domain-inactivated (R347A) TNFR1, and in SK-HEP-1 cells transfected with normal (full-length) TNFR1, cytokine production stimulated in the absence of exogenous TNF by the presence of certain TNFR1 variants was not inhibited by the anti-TNFR1 dAb. In SK-Hep-1 cells, specific TRAPS mutations increased the level of cytokine response to TNF, compared to WT, and this augmented cytokine production was suppressed by the anti-TNFR1 dAb. Thus, TRAPS-associated variants of TNFR1 enhance cytokine production by a TNF-independent mechanism and by sensitising cells to a TNF-dependent stimulation. The TNF-dependent mechanism requires cell surface expression of TNFR1, as this is blocked by TNFR1-specific dAb.